2020
DOI: 10.1177/2192568220947744
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Spine Examination: Telemedicine in the Era of COVID-19 and Beyond

Abstract: Study Design: Narrative review. Objectives: Describe a comprehensive spine telemedicine examination. Methods: We discuss telemedicine examination techniques for commonly encountered spine conditions. Results: Techniques to evaluate gait, the cervical spine, the lumbar spine, adult spinal deformity patients, and adolescent scoliosis patients via telemedicine are described. We review limitations of the spine telemedicine examination and discuss special considerations such as patient safety and criteria for in-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 33 publications
0
53
2
Order By: Relevance
“…External forces limiting in-person evaluations forced orthopaedic providers to carve out a novel role for telemedicine in the pre-operative assessment of patients, and challenged the perceptions of many patients, providers, and healthcare systems. Specifically, much of the literature thus far has focused on the use and validity of various virtual physical exam manoeuvres [ 5 10 ]. However, given the significant breakthroughs in advanced imaging, technology, and communications systems, it is not clear that the physical exam itself is as important as it once was for most orthopaedic diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…External forces limiting in-person evaluations forced orthopaedic providers to carve out a novel role for telemedicine in the pre-operative assessment of patients, and challenged the perceptions of many patients, providers, and healthcare systems. Specifically, much of the literature thus far has focused on the use and validity of various virtual physical exam manoeuvres [ 5 10 ]. However, given the significant breakthroughs in advanced imaging, technology, and communications systems, it is not clear that the physical exam itself is as important as it once was for most orthopaedic diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…The primary limitation of telemedicine is the inability to perform a traditional in-person physical examination, which has long been taught to be paramount to the accurate diagnosis and treatment of musculoskeletal pathologies. As such, much of the recent clinical telemedicine literature within orthopaedics has focused on addressing and adapting to this limitation, with innovative virtual alternatives to traditional exams [ 5 10 ]. Nonetheless, these virtual exams have yet to be validated and standardised.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the most substantial challenge was the decreased ability to perform the physical examination, with nearly 40% of respondents highlighting this issue. Recent manuscripts have sought to address this challenge by publishing guidelines how to conduct effective virtual spine examinations [13,16]. Additionally, efforts to enhance the telemedicine appointment-such as providing instructions for patients prior to the visit on camera/body positioning, clothing, and setting-have shown to increase telemedicine efficiency [17,18].…”
Section: Challengesmentioning
confidence: 99%
“…There are now several publications that describe a virtual neurologic examination [ 44 , 45 ]. There is also a growing number of publications addressing the possibility of virtual spine examination [ 46 , 47 , 48 ], although none of these virtual examinations have been studied for validity or reliability.…”
Section: Discussionmentioning
confidence: 99%